Insights into Implementation of National Agricultural Market scheme in Telangana - Singh, Shalendra; Paty, B K (Journal of Agricultural Extension Management, 2019)
A common market for agricultural produce in India is an idea at a time whenagricultural marketing is faced with many challenges. An ICT based commonmarket has the potential to address such limitations. Accordingly, the concept ofelectronic National Agricultural Market (eNAM) has been introduced by the UnionGovernment. An attempt has been made, in the present paper, to understand the implementation of eNAM and assess its ability to live up to its potential. Theobservations made in selected markets in Telangana in terms of capturing arrivals, electronic price discovery and shortening of trade cycle hours triggers the hope for development of an agricultural market operating at the national level. The concept has the potential to catalyse the overall development of the sector, if over time, it is able to move beyond application of information technology by having a holistic development of the marketing system covering its different aspects. It is required to be pursued as a means and not as an end in itself and must be made to evolve accordingly.